(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Bituminous concrete mix is a composite material which is widely used for the construction of flexible pavements, surfacing of roads and airports, various parking lots etc. It generally consists of bitumen which works as a binder material, coarse aggregates, fine aggregates and filler materials which are generally mixed together in right proportion and laid down in layers followed by the compaction. In this present age of modernization and urbanization, construction is non stoppable and the construction by demolishing of old building has arisen a serious problem of treatment of demolished waste. Similarly, the use of plastic in our day to-day life and its improper disposal is also creating serious environment pollution. So, there is big challenge in managing the demolished waste as well as the waste plastics. In this project i.e. partial replacement of RCA and LDPE in Bituminous concrete mix we have tried to replace the RCA (25%) in Natural Aggregates and LDPE (2%, 4%, 6% and 8% respectively) in bitumen content for the improvement of the pavement characteristics satisfying both the strength criteria and the economic aspectsgiving emphasize to less environment degradation and sustainability.